Kesalahan Mahasiswa dalam Menyelesaikan Masalah Penjumlahan Vektor Secara Analitis dan Secara Grafis Berbantuan Aplikasi Geogebra - Martin, Sri Novia; Nazarlin, Nazarlin (Imajiner: Jurnal Matematika dan Pendidikan Matematika, 2025)
The purpose of this study is to describe the difficulties experienced by students when solving vector addition problems analitically and graphically. In solving problems related to vector summation, there are two ways that can be used, namely analytically and graphically. Analytically, it is to decompose vectors into their components and then look for the response. Meanwhile, graphically using the help of Geogebra and using the concept of Triangle. Then in each way analyzed the difficulties experienced by students. This research method is descriptive qualitative. Data were obtained from observation, interviews, and tests. The subject of research was 38 UNP mathematics education students. The data obtained were analyzed using Miles and Huberman's measures of data reduction, data display and conclusions. The results of the study obtained information analytically the difficulties faced by students are interpreting / illustrating problems or problems into images or symbols, choosing strategies for solving (the right formula), miscalculations, and not making answer conclusions, not checking back on the answers that have been obtained. Meanwhile, graphically using the Geogebra application the difficulty experienced is interpreting it into the form of mathematical images / symbols, making accurate measurements of vector lengths or angles and not making answer conclusions.